Survey on VoIP transmission in 3GPP standards - Gayathri Devi K. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This article, presents that how do voice calls deliver for the PSTN/Cellular quality VoIP services over WiMax networks. The good MOS (Mean Opioin score) value is obtained using the OPNET simulator. Video streaming service’s provides end to end connectivity in IP based transmission. The main objective of the article is to investigate the voice quality parameters and WiMax network management services during a hierarchical simulation status. VoIP (voice over internet Protocol) is one of the user interfaced application layered protocol, which is used in the proposed work and voice call is established; Initiate; call connect among the number of mobile users. This model provides jitter and delay in voice calls; throughput and interact with mobile users; prevention of miscellaneous node; in peer to peer coverage area. The simulation test bench performances were appropriated by our WAN coverage area.